A fast technique using output only to localize and quantify multiple damages for multi-degree-of-freedom systems. (January 2021) - Cheng, Liangliang; Fang, Wenshan; Zhu, Yunpeng
Vibration-based methods for identifying and evaluating structural damages have been widely studied in the last decades. However, in the state-of-art methods, there are some practical limitations owing to the complicated calculation process and low damage sensitivities. A new method for localizing and quantifying the damages of a beam-like structure based on low-frequency components, including direct current component, of the output signal subject to an arbitrary input excitation, is proposed in this article. The relationship between the low-frequency components of any two adjacent measurement points is investigated, in order to help to understand the link between damages and low-frequency components of outputs. The theoretical derivation of this method begins with a multi-degree-of-freedom structure of the mass–spring–damper chain, and the damage is considered to be a linear combination of local stiffness losses, resulting in changes in structural dynamic behaviors. The validity and feasibility of the proposed damage indicators are proved by numerical and experimental studies. It is further shown that the severity of the damage can be properly identified using the proposed damage indicator. Moreover, a discussion concerning potential detection on multiple nonlinear damages is presented at the end of this article.